Sharia Economic Law's View on Online Loans (Spinjam) on the Shopee Application - Fithriya Khusna Khamidah (Santara: Journal of Islamic Law and Humanity, 2025)
This study aims to analyze the practice of SPinjam online loans on the Shopee application and the views of sharia economic law on the service. SPinjam is an information technology-based financing service that allows users to access loans with a fast and easy process. However, this practice raises questions related to its compliance with sharia economic principles, especially regarding the application of interest, administration fees, and late fees. This study uses a qualitative descriptive approach with a literature study as a data collection method. Data sources were obtained from books, scientific journals, DSN MUI fatwas, and related articles. The research findings show that although SPinjam facilitates access to loans, there is a discrepancy between the loan practice and sharia principles, especially in terms of the application of interest and late fees which are considered usury. The contract used in SPinjam is not entirely in accordance with the principle of qardh contracts in sharia, which prohibits additional costs or interest on loans. This study contributes to enriching the understanding of fintech applications in the context of sharia economic law and provides recommendations for online loan providers to pay more attention to the principles of justice and compliance with sharia. This study also identified existing limitations, particularly in terms of secondary data collection, and suggested further research involving direct interviews with users and practitioners.